Kebijakan Dalam Inovasi Pendidikan - Syafira Syafira; Fella Annisa Harahap; Tasya Zuraira; Nuria Tri Utami; Oktrigana Wirian (Universitas Katolik Widya Karya Malang, 2023)
Education policy in Indonesia over time has experienced various significant dynamics. The purpose of this change in education policy is none other than to create quality education. This research was conducted in order to fulfill the duties of the Educational Innovation Course, and aims to find out the Policy in Educational Innovation and to train writers to conduct mini research. This research was conducted in order to fulfill the duties of the Educational Innovation Course, and aims to find out the Policy in Educational Innovation and to train writers to conduct mini research. Open schools are a solution for children who are far from the main school due to geographical conditions that are difficult to reach by public transportation, due to economic factors in some communities which are weak so they have to work even though they are still of school age between 13-18 years after graduating from elementary school.